Heat treatment process for spray-formed high-lithium-content aluminum-lithium alloy

Aluminum-lithium alloys with high lithium content are prepared through injection molding technology, and the heat treatment process of slow-rate temperature rise, two-stage homogenization, two-stage solid solution, cold deformation, and two-stage aging solves the problem of poor plasticity and toughness of materials in traditional casting methods. , achieving comprehensive mechanical properties of high strength and high plastic toughness.

CN119351907APending Publication Date: 2025-01-24JIANGSU HAORAN SPRAY FORMING ALLOY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411238149.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When preparing aluminum-lithium alloys by traditional casting methods, a large number of lithium-containing intercrystalline compounds will be generated at the grain boundary when the lithium content exceeds 2.8%, resulting in poor plastic toughness of the material and difficult to achieve comprehensive mechanical properties of high strength and high plastic toughness.

Method used

The high lithium content aluminum-lithium alloy is prepared using injection molding technology, and through the heat treatment process of slow-rate temperature rise, dual-stage homogenization, dual-stage solid solution, cold deformation, and dual-stage aging, the material structure is optimized to maximize the uniform distribution and size of the precipitation. Tiny main strengthening phase.

Benefits of technology

The high strength and high -plastic toughness of the aluminum alloy aluminum alloy of the high -lithium content of the jet shall be achieved. The density is less than 2.40g/cm3, the tensile strength is greater than 520MPa, the yield strength is greater than 470MPa, and the extension rate is greater than 6 %.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a heat treatment method for spray forming of a high-lithium-content aluminum-lithium alloy. The heat treatment method comprises the steps of two-stage homogenization, two-stage solid solution, cold deformation and two-stage aging treatment of the spray-formed high-lithium-content aluminum-lithium alloy. According to the two-stage homogenization process provided by the invention, grain boundary segregation is greatly reduced, and meanwhile, precipitation of a second phase of rare earth is promoted. According to the two-stage solution treatment provided by the invention, the number of non-equilibrium eutectic phases in the high-lithium-content aluminum-lithium alloy is greatly reduced. According to the cold deformation and two-stage aging treatment provided by the invention, precipitation of multiple strengthening phases is promoted, meanwhile, the size of a precipitated phase is reduced, and the alloy is promoted to obtain good comprehensive mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat treatment of aluminum alloys, and relates to a heat treatment method for a spray-formed aluminum-lithium alloy with a high lithium content. Background Art

[0002] Aluminum-lithium alloy is a lightweight, high-performance aluminum alloy material that is of great significance to the lightweighting of aerospace equipment. Compared with traditional high-strength aviation aluminum alloys, aluminum-lithium alloy can reduce the overall weight of aircraft by 10%-20%. Every 1% of lithium added to the aluminum alloy can reduce the density of the aluminum alloy by 3% and increase the elastic modulus by 6%. However, when aluminum-lithium alloy is prepared by traditional casting methods, when the lithium content exceeds 2.8%, a large amount of lithium-containing intergranular compounds will be generated at the grain boundaries, resulting in poor plastic toughness of the material.

[0003] The rapid solidification spray forming technology can break through the traditional casting lithium content limit, and add Mg, Cu, Mn, Zn, Zr and other alloying elements at the same time, with the protection of inert gas, it can produce large-scale high lithium content aluminum-lithium alloy with uniform composition, fine structure and low hydrogen content. The second phases that may precipitate in this multi-element, high alloying content aluminum-lithium alloy include δ'(Al3Li) phase, θ'(Al2Cu) phase, T1(Al2CuLi) phase, S'(Al2CuMg) phase, β'(Al3Zr) phase, T(Al2MgLi) phase, T2(Al6CuLi3) phase, etc. In order to achieve a material with both high strength and plasticity and toughness, it is necessary to achieve fine-grained control of the material structure through heat treatment, to precipitate the main strengthening phase δ' phase with uniform distribution and small size in the matrix to the maximum extent, and to precipitate the θ' phase, T1 phase, and β' phase to supplement the strengthening, and to reduce the influence of coplanar slip in high-Li content aluminum-lithium alloys, while controlling the precipitation of larger-sized lamellar T1 phase at the grain boundaries.

[0004] Therefore, the development of heat treatment process for high lithium content aluminum-lithium alloy prepared by injection forming technology is the key to achieving high strength and high toughness comprehensive mechanical properties of high lithium content aluminum-lithium alloy. Summary of the invention

[0005] The purpose of the present invention is to develop a heat treatment process for high-lithium-content aluminum-lithium alloys of spray-forming technology equipment, which uses slow heating rate two-stage homogenization, two-stage solid solution, cold deformation, and two-stage aging as process conditions to obtain high-strength and high plasticity and toughness aluminum-lithium alloys with high lithium content.

[0006] In order to achieve the above object, the technical solution steps adopted by the present invention are:

[0007] (1) Homogenization treatment: After the spray-formed high-lithium content aluminum-lithium alloy ingot is sealed and wrapped, it is placed in a furnace at room temperature, and the temperature is slowly increased to 350-420°C, and kept at this temperature for 2-10 hours; the temperature is further slowly increased to 450-520°C, and kept at this temperature for 12-36 hours, and then air-cooled;

[0008] (2) Solution treatment: heat the hot-deformed spray-formed high-lithium content aluminum-lithium alloy to 350-450°C and keep it for 2-8 hours, then heat it to 500-560°C and keep it for 1-10 hours; quench after solution treatment;

[0009] (3) Cold deformation treatment: cold deformation treatment is performed on the spray-formed high lithium content aluminum-lithium alloy sheet or profile after solid solution;

[0010] (4) Aging treatment: The cold-deformed alloy is heated to 110-140°C in a heat treatment furnace for 2-12 hours, and then heated to 150-250°C for 8-24 hours.

[0011] Further preferably, the chemical composition of the injection-formed high-lithium-content aluminum-lithium alloy is 3.0-8.5wt.% Li, 1.0-6.5wt.% Mg, 0.1-1.0wt.% Cu, 0.05-0.50wt.% Mn, 0.1-0.50wt.% Zn, 0.05-0.30wt.% Zr, and the remainder is Al, with a total mass percentage of 100%.

[0012] Further preferably, the total amount of impurity elements Fe, Si, Na, and K in the injection-formed high-lithium-content aluminum-lithium alloy is less than 0.25wt.%, of which Fe is less than 0.15wt.%, and Si is less than 0.10wt.%.

[0013] More preferably, the heating rate of the homogenization slow heating in step (1) is 5 to 50° C. / h.

[0014] Further preferably, the alloy is sealed by wrapping with industrial aluminum foil during the homogenization treatment in step (1).

[0015] More preferably, the post-solution quenching method in step (2) is water quenching, and the water temperature is room temperature to 60°C.

[0016] More preferably, the cold deformation in step (3) is stretching deformation or rolling deformation, and the deformation amount is 2% to 8%.

[0017] The advantages and beneficial effects of the present invention are:

[0018] (1) The present invention designs a two-stage homogenization system with slow heating rate in view of the characteristics of high lithium content and multi-element alloyed aluminum-lithium alloys formed by injection molding. On the one hand, it can promote the precipitation of Al3 (Sc, Zr) phase during the slow heating rate process, thereby inhibiting recrystallization and grain growth during subsequent hot working deformation. On the other hand, since high lithium content is prone to segregation, the present invention designs homogenization at different temperatures to maximize the dissolution of the second phase, promote composition homogenization, and inhibit excessive grain growth. In addition, in view of the porous characteristics of injection-formed deposited materials, the present invention uses aluminum foil to seal and wrap the alloy during the homogenization process, which can effectively prevent obvious oxidation during the homogenization process of high lithium content alloys.

[0019] (2) Aiming at the characteristics of high lithium content aluminum-lithium alloy in spray forming, which has many kinds of elements and high content, the present invention designs a two-stage solid solution system and optimizes the solid solution temperature and time in a graded manner, which maximizes the dissolution of different types of intergranular compounds, improves the supersaturation of the matrix, and prevents excessive growth of grains. After solid solution, the quenching temperature is optimized to prevent cracking of the material during the quenching process.

[0020] (3) The present invention designs cold deformation before aging and optimizes the deformation amount, which greatly increases the dislocation density inside the material, provides more non-uniform nucleation sites for the precipitation of the main strengthening phase, promotes the uniform and fine distribution of the main strengthening phase, and thus optimizes the comprehensive mechanical properties of the alloy.

[0021] (4) The present invention promotes the coordinated precipitation of the primary strengthening phase and the secondary strengthening phase by designing a two-stage aging system, weakens the influence of the coplanar slip of the δ'(Al3Li) phase, reduces the anisotropy of the material, and reduces the precipitation of the intergranular non-equilibrium phase, thereby further optimizing the comprehensive mechanical properties of the alloy.

[0022] (5) After the heat treatment process of the present invention is used to heat treat the spray-formed high-lithium content aluminum-lithium alloy extruded profiles or rolled plates, the aluminum-lithium alloy density can be less than 2.40 g / cm 3 , while the tensile strength is greater than 520MPa, the yield strength is greater than 470MPa, and the elongation is greater than 6%. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] The high lithium content aluminum-lithium alloy ingot used in this embodiment is prepared by spray forming technology, and its chemical composition and weight percentage are: Li 3.8wt.%, Mg 2.0wt.%, Cu 0.5wt.%, Mn 0.25wt.%, Zn 0.25wt.%, Zr0.1wt.%, Al 93.1wt.%.

[0026] (1) Homogenization treatment: The spray-formed ingots with the above composition are sealed with industrial aluminum foil and placed in a furnace at room temperature. The temperature is raised to 400°C at a rate of 25°C / h and kept at this temperature for 6 hours; the temperature is further raised to 500°C at a rate of 25°C / h and kept at this temperature for 24 hours. After the heat preservation is completed, the ingots are taken out and air-cooled to room temperature. The homogenized ingots are extruded into rods at 450°C.

[0027] (2) Solution treatment: The spray-formed high-lithium-content aluminum-lithium alloy after hot extrusion deformation is heated to 350°C and kept at this temperature for 5 hours, then heated to 525°C and kept at this temperature for 1.5 hours. After solution treatment, it is quenched at room temperature.

[0028] (3) Cold deformation treatment: The solution-solution-formed high-lithium-content aluminum-lithium alloy extrusions are pre-stretched on a stretching machine with a deformation amount of 2%.

[0029] (4) Aging treatment: The cold-deformed alloy was heated to 120°C in a heat treatment furnace for 8 hours, and then heated to 190°C for 8 hours. After the insulation, the alloy was taken out and air-cooled to room temperature. The sample was then stretched at room temperature, and the tensile strength, yield strength and elongation of the heat-treated sample were tested. The test results are shown in Table 1.

[0030] Example 2

[0031] The high lithium content aluminum-lithium alloy ingot used in this embodiment is prepared by spray forming technology, and its chemical composition and weight percentage are: Li 4.0wt.%, Mg 1.0wt.%, Cu 0.8wt.%, Mn 0.20wt.%, Zn 0.15wt.%, Zr 0.2wt.%, Al

[0032] 93.65wt.%.

[0033] (1) Homogenization treatment: The spray-formed ingots with the above composition are sealed with industrial aluminum foil and placed in a furnace at room temperature. The temperature is raised to 375°C at a rate of 30°C / h and kept at this temperature for 5 hours; the temperature is further raised to 510°C at a rate of 30°C / h and kept at this temperature for 20 hours. After the heat preservation is completed, the ingots are taken out and air-cooled to room temperature. The homogenized ingots are rolled into plates at 465°C.

[0034] (2) Solution treatment: Heat the rolled plate to 400°C and keep it for 2 hours, then heat it to 550°C and keep it for 1 hour. After solution treatment, quench at room temperature.

[0035] (3) Cold deformation treatment: The solution-solutionized spray-formed high-lithium-content aluminum-lithium alloy rolled plate is subjected to rolling deformation with a deformation amount of 4%.

[0036] (4) Aging treatment: The cold-deformed alloy was heated to 130°C in a heat treatment furnace for 8 hours, and then heated to 170°C for 12 hours. After the insulation, the alloy was taken out and air-cooled to room temperature. The sample was then stretched at room temperature, and the tensile strength, yield strength and elongation of the heat-treated sample were tested. The test results are shown in Table 1.

[0037] Comparative Example 1

[0038] The same materials as in Example 1 were used for the following treatment:

[0039] (1) Homogenization treatment: The spray-formed ingots with the above composition are placed in a furnace at room temperature without wrapping and protection, and the temperature is raised to 400°C at a rate of 25°C / h and kept at this temperature for 6 hours; the temperature is further raised to 500°C at a rate of 25°C / h and kept at this temperature for 24 hours. After the end of the heat preservation, the ingots are taken out and air-cooled to room temperature. The homogenized ingots are extruded into rods at 450°C.

[0040] (2) Solution treatment: The spray-formed high-lithium-content aluminum-lithium alloy after hot extrusion deformation is heated to 350°C and kept at this temperature for 5 hours, then heated to 525°C and kept at this temperature for 1.5 hours. After solution treatment, it is quenched at room temperature.

[0041] (3) Cold deformation treatment: The solution-solution-formed high-lithium-content aluminum-lithium alloy extrusions are pre-stretched on a stretching machine with a deformation amount of 2%.

[0042] (4) Aging treatment: The cold-deformed alloy was heated to 120°C in a heat treatment furnace for 8 hours, and then heated to 190°C for 8 hours. After the insulation, the alloy was taken out and air-cooled to room temperature. The sample was then stretched at room temperature, and the tensile strength, yield strength and elongation of the heat-treated sample were tested. The test results are shown in Table 1.

[0043] Comparative Example 2

[0044] The same materials as in Example 1 were used for the following treatment:

[0045] (1) Homogenization treatment: The spray-formed ingots with the above composition are sealed with industrial aluminum foil and placed in a furnace at room temperature. The temperature is raised to 500°C at a rate of 25°C / h and kept at this temperature for 24 hours. After the heat preservation, the ingots are taken out and air-cooled to room temperature. The homogenized ingots are extruded into rods at 450°C.

[0046] (2) Solution treatment: The spray-formed high-lithium-content aluminum-lithium alloy after hot extrusion deformation is heated to 350°C and kept at this temperature for 5 hours, then heated to 525°C and kept at this temperature for 1.5 hours. After solution treatment, it is quenched at room temperature.

[0047] (3) Cold deformation treatment: The solution-solutionized high-lithium aluminum-lithium alloy extrusions were pre-stretched on a stretching machine with a deformation of 2%. (4) Aging treatment: The cold-deformed alloy was heated to 120°C in a heat treatment furnace and kept warm for 10 hours, then heated to 190°C and kept warm for 8 hours. After the insulation, the alloy was taken out and air-cooled to room temperature. The sample was then stretched at room temperature, and the tensile strength, yield strength and elongation of the heat-treated sample were tested. The test results are shown in Table 1.

[0048] Comparative Example 3

[0049] The same materials as in Example 1 were used for the following treatment:

[0050] (1) Homogenization treatment: The spray-formed ingots with the above composition are sealed with industrial aluminum foil and placed in a furnace at room temperature. The temperature is raised to 400°C at a rate of 100°C / h and kept at this temperature for 6 hours; the temperature is further raised to 500°C at a rate of 100°C / h and kept at this temperature for 24 hours. After the heat preservation is completed, the ingots are taken out and air-cooled to room temperature. The homogenized ingots are extruded into rods at 450°C.

[0051] (2) Solution treatment: The spray-formed high-lithium-content aluminum-lithium alloy after hot extrusion deformation is heated to 350°C and kept at this temperature for 5 hours, then heated to 525°C and kept at this temperature for 1.5 hours. After solution treatment, it is quenched at room temperature.

[0052] (3) Cold deformation treatment: The solution-solution-formed high-lithium-content aluminum-lithium alloy extrusions are pre-stretched on a stretching machine with a deformation amount of 2%.

[0053] (4) Aging treatment: The cold-deformed alloy was heated to 120°C in a heat treatment furnace for 8 hours, and then heated to 190°C for 8 hours. After the insulation, the alloy was taken out and air-cooled to room temperature. The sample was then stretched at room temperature, and the tensile strength, yield strength and elongation of the heat-treated sample were tested. The test results are shown in Table 1.

[0054] Comparative Example 4

[0055] The same materials as in Example 1 were used for the following treatment:

[0056] (1) Homogenization treatment: The spray-formed ingots with the above composition are sealed with industrial aluminum foil and placed in a furnace at room temperature. The temperature is raised to 400°C at a rate of 25°C / h and kept at this temperature for 6 hours; the temperature is further raised to 500°C at a rate of 25°C / h and kept at this temperature for 24 hours. After the heat preservation is completed, the ingots are taken out and air-cooled to room temperature. The homogenized ingots are extruded into rods at 450°C.

[0057] (2) Solution treatment: The spray-formed high-lithium-content aluminum-lithium alloy after hot extrusion deformation is heated to 350°C and kept at this temperature for 5 hours, then heated to 525°C and kept at this temperature for 1.5 hours. After solution treatment, it is quenched at room temperature.

[0058] (3) Aging treatment: The cold-deformed alloy was heated to 120°C in a heat treatment furnace for 8 hours, and then heated to 190°C for 8 hours. After the insulation, the alloy was taken out and air-cooled to room temperature. The sample was then stretched at room temperature, and the tensile strength, yield strength and elongation of the heat-treated sample were tested. The test results are shown in Table 1.

[0059] Comparative Example 5

[0060] The same materials as in Example 2 were used for the following treatment:

[0061] (1) Homogenization treatment: The spray-formed ingots with the above composition are sealed with industrial aluminum foil and placed in a furnace at room temperature. The temperature is raised to 375°C at a rate of 30°C / h and kept at this temperature for 5 hours; the temperature is further raised to 510°C at a rate of 30°C / h and kept at this temperature for 20 hours. After the heat preservation is completed, the ingots are taken out and air-cooled to room temperature. The homogenized ingots are rolled into plates at 465°C.

[0062] (2) Single-stage solution treatment: heat the rolled plate to 525°C and keep it at this temperature for 1.5 h.

[0063] (3) Cold deformation treatment: The solution-solutionized spray-formed high-lithium-content aluminum-lithium alloy rolled plate is subjected to rolling deformation with a deformation amount of 4%.

[0064] (4) Aging treatment: The cold-deformed alloy was heated to 130°C in a heat treatment furnace for 8 hours, and then heated to 170°C for 12 hours. After the insulation, the alloy was taken out and air-cooled to room temperature. The sample was then stretched at room temperature, and the tensile strength, yield strength and elongation of the heat-treated sample were tested. The test results are shown in Table 1.

[0065] Comparative Example 6

[0066] The same materials as in Example 2 were used for the following treatment:

[0067] (1) Homogenization treatment: The spray-formed ingots with the above composition are sealed with industrial aluminum foil and placed in a furnace at room temperature. The temperature is raised to 375°C at a rate of 30°C / h and kept at this temperature for 5 hours; the temperature is further raised to 510°C at a rate of 30°C / h and kept at this temperature for 20 hours. After the heat preservation is completed, the ingots are taken out and air-cooled to room temperature. The homogenized ingots are rolled into plates at 465°C.

[0068] (2) The rolled plate is heated to 400°C and kept at this temperature for 2 hours, then heated to 550°C and kept at this temperature for 1 hour. After solution treatment, it is quenched at room temperature.

[0069] (3) Cold deformation treatment: The solution-solutionized spray-formed high-lithium-content aluminum-lithium alloy rolled plate is subjected to rolling deformation with a deformation amount of 4%.

[0070] (4) Aging treatment: The alloy after cold deformation was heated to 190°C in a heat treatment furnace and kept at this temperature for 10 hours. After the heat preservation, the alloy was taken out and air-cooled to room temperature. The sample was then stretched at room temperature, and the tensile strength, yield strength and elongation of the heat-treated sample were tested. The test results are shown in Table 1.

[0071] Comparing Example 1 and Comparative Example 1, when the spray-formed high-lithium-content aluminum-lithium alloy ingot is homogenized in an air atmosphere furnace, due to the high lithium content and the presence of pores in the sprayed ingot, if it is not sealed and wrapped with aluminum foil, it is very easy to cause lithium burnout on the surface of the ingot and oxidation around the pores during the homogenization process, thereby resulting in reduced strength and plastic toughness.

[0072] Comparing Example 1 with Comparative Example 2, compared with single-stage homogenization, double-stage homogenization has a better effect on reducing the segregation of alloy elements in the ingot.

[0073] Comparing Example 1 and Comparative Example 3, compared with the fast rate heating homogenization, reducing the homogenization heating rate can promote the precipitation of Al3Zr phase, thereby having a better effect of inhibiting thermal deformation recrystallization and grain growth.

[0074] Comparing Example 1 and Comparative Example 4, compared with not cold deforming before aging, pre-deformation can increase dislocations, has a deformation strengthening effect, and provides more non-uniform nucleation points for the precipitation of dispersed phases.

[0075] Comparing Example 2 with Comparative Example 5, compared with the single-stage solid solution, the second phase dissolution effect after the double-stage solid solution is better, which can increase the supersaturation of the matrix, thereby precipitating more strengthening phases in the subsequent aging process.

[0076] Comparing Example 2 and Comparative Example 6, compared with single-stage aging, double-stage aging can regulate the precipitation order of different dispersed phases in the alloy, synergistically precipitate multiple strengthening phases, reduce the influence of coplanar slip, reduce the width of the intergranular precipitation-free zone, and improve the comprehensive mechanical properties of the alloy.

[0077] Table 1 Mechanical properties of examples and comparative examples

[0078]

[0079]

[0080] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0082] The above embodiments are only used to illustrate the present invention and are not used to limit the protection scope of the present invention. For those skilled in the art, improvements can be made without departing from the principle of the present invention, and these improvements should also be considered as the protection scope of the present invention.

Claims

1. A heat treatment process for spray-formed high lithium content aluminum-lithium alloy, characterized in that: The specific steps include: (1) Homogenization treatment: After the spray-formed high-lithium content aluminum-lithium alloy ingot is sealed and wrapped, it is placed in a furnace at room temperature, and the temperature is slowly increased to 350-420°C, and kept at this temperature for 2-10 hours; the temperature is further slowly increased to 450-520°C, and kept at this temperature for 12-36 hours, and then air-cooled; (2) Solution treatment: Heat the hot-deformed spray-formed high-lithium content aluminum-lithium alloy to 350-450°C and keep it for 2-8 hours, then heat it to 500-560°C and keep it for 1-10 hours. After solution treatment, quenching is performed; (3) Cold deformation treatment: cold deformation treatment is performed on the spray-formed high lithium content aluminum-lithium alloy sheet or profile after solid solution; (4) Aging treatment: The cold-deformed alloy is heated to 110-140°C in a heat treatment furnace for 2-12 hours, and then heated to 150-250°C for 8-24 hours.

2. The heat treatment process of spray-formed high lithium content aluminum-lithium alloy according to claim 1 is characterized in that: The element composition of the injection-formed high-lithium-content aluminum-lithium alloy is as follows: 3.0-8.5wt.% Li, 1.0-6.5wt.% Mg, 0.1-1.0wt.% Cu, 0.05-0.50wt.% Mn, 0.1-0.50wt.% Zn, 0.05-0.30wt.% Zr, and the remainder is Al, with a total mass percentage of 100%.

3. The heat treatment process of spray-formed high lithium content aluminum-lithium alloy according to claim 1, characterized in that: The total amount of impurity elements Fe, Si, Na and K in the injection-formed high-lithium-content aluminum-lithium alloy is less than 0.25wt.%, of which Fe is less than 0.15wt.% and Si is less than 0.10wt.%.

4. The heat treatment process of spray-formed high lithium content aluminum-lithium alloy according to claim 1, characterized in that: The heating rate of the slow heating in the homogenization treatment of step (1) is 5 to 50° C. / h.

5. The heat treatment process of spray-formed high lithium content aluminum-lithium alloy according to claim 1, characterized in that: During the homogenization treatment in step (1), the alloy is sealed by wrapping with industrial aluminum foil.

6. The heat treatment process of spray-formed high lithium content aluminum-lithium alloy according to claim 1, characterized in that: The quenching method after the solutionizing in step (2) is water quenching, and the water temperature is room temperature to 60°C.

7. The heat treatment process of spray-formed high lithium content aluminum-lithium alloy according to claim 1, characterized in that: The cold deformation method in step (3) is stretching deformation or rolling deformation, and the deformation amount is 2% to 8%.